(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
This article test the effect of providing face-to-face information on anxiety and physiological measures of patients undergoing third molars extraction. The study included 123 patients divided into: experimental group (EG) and control group (CG). The instruments used were: the Dental Anxiety Scale (DAS) and the State-Trait Anxiety Inventory (STAI). Assessment of anxiety occurred in the stages: Pre-Surgical, Immediate Post-Surgical, Mediate Post-Surgical and Suture Removal. Physiological assessment occurred in the stages: Pre-Surgical, Immediate Post-Surgical and Suture Removal. Face-to-face information was only offered to the EG immediately after the first stage. We used the Chi-square test, mixed models for repeated measures (Proc Mixed of the SAS program) and Tukey (α=5%). There were no statistically significant differences between groups on anxiety and physiological measures. However, patients’ systolic and diastolic blood pressures and their anxiety scores were lower in the EG than the CG, which suggests an effect of the preparatory procedure.